Pembangkit Listrik Menggunakan Generator Termoelektrik pada Dinding Model Bangunan - Rifky; Reza Ferizal Akbar; Oktarina Heriyani; Riyan Ariyansah; Akhmad Rizal Dzikrillah (Fakultas Teknik, Universitas Muhammadiyah Prof. Dr. Hamka, Jakarta, 2024)
This research was initiated by the idea of making building materials and/or building components/parts into sources of electrical energy, especially on the roof and walls of buildings. Building roofs and walls have the potential as a means of utilizing solar energy into electrical energy with a thermoelectric generator (TEG) converter. Therefore, the aim of this research is to obtain the performance of thermoelectric generators with series and parallel circuits as power generators on the walls of building models. The research methodology used is experimental which begins with designing research equipment consisting of a building model frame and a thermoelectric system arrangement. In this research, a series and parallel TEG circuit was compared. Both sets of TEG systems have aluminum attached to absorb heat from the sun on the hot side of the TEG and a water block made of aluminum is attached to the cold side of the TEG. Styrofoam is attached to the surrounding sides between the TEG modules as a thermal insulator. The parameters in this research consist of independent variables, moderator variables and dependent variables. The independent variables are the temperature of the hot side of the TEG and the temperature of the cold side of the TEG. The moderator variables are good water temperature, water discharge, water temperature entering the waterblock, water temperature leaving the waterblock. Meanwhile, the dependent variables are electric current strength, electric voltage, electric power, and TEG efficiency. The research results showed that the maximum electric current was 0.54 A and the maximum electric voltage was 0.08 V. The maximum electric power as output power from the TEG system was 0.0432 W and the average thermoelectric efficiency was 4%.